Larvicide activity of ethanol extracts from Zodia (Evodia suaveolens S.) leaves and Cananga (Cananga odorata) flowers on Aedes aegypti larvae - Dewi, Purista Tiara; Dewi, Listiana Masyita (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Controlling Aedes aegypti population in Dengue management programs is often carried out using high doses of synthetic insecticides, such as temephos, that may lead to resistances. An alternative of natural ingredient such as Zodia (Evodia suaveolens S.) leaves, that containing evodiamine and Cananga (Cananga odorata) flower that containing linalool, appears to be a promising larvicide. This study aims to determine the effectivity of ethanol extracts from Zodia leaves and Cananga flowers on the mortality of Aedes aegypti larvae. This experimental study using Aedes aegypti larvae at stage of III-IV. Each ingredient was extracted by the maceration method and then prepared at concentration of 2.5% and 5%. PEG 400 was also added as a diluent. Observations performed every 6 hours, for 24 hours. Data analysis using Kruskal Wallis test and Dunn's test. Within 24 hours, in each of study group, there was 100% larval mortality. The Kruskal Wallis test resulting p-value of <0.05. From Dunn’s test, comparisons between each study group and the negative and positive control groups yielded p-values <0.05 and 1.000, respectively. Thus, it can be said that ethanol extracts from Zodia leaves and Cananga flowers are as effective as temephos as larvicide on Aedes aegypti larvae